A synthetic three-dimensional niche system facilitates generation of functional hematopoietic cells from human-induced pluripotent stem cells. Issue 1 (December 2016) - Xu, Yulin; Shan, Wei; Li, Xia; Wang, Binsheng; Liu, Senquan; Wang, Yebo; Long, Yan; Tie, Ruxiu; Wang, Limengmeng; Cai, Shuyang; Zhang, Hao; Lin, Yu; et al.
Abstract Background The efficient generation of hematopoietic stem cells (HSCs) from human-induced pluripotent stem cells (iPSCs) holds great promise in personalized transplantation therapies. However, the derivation of functional and transplantable HSCs from iPSCs has had very limited success thus far. Methods We developed a synthetic 3D hematopoietic niche system comprising nanofibers seeded with bone marrow (BM)-derived stromal cells and growth factors to induce functional hematopoietic cells from human iPSCs in vitro. Results Approximately 70 % of human CD34+ hematopoietic cells accompanied with CD43+ progenitor cells could be derived from this 3D induction system. Colony-forming-unit (CFU) assay showed that iPSC-derived CD34+ cells formed all types of hematopoietic colonies including CFU-GEMM.TAL-1 andMIXL1, critical transcription factors associated with hematopoietic development, were expressed during the differentiation process. Furthermore, iPSC-derived hematopoietic cells gave rise to both lymphoid and myeloid lineages in the recipient NOD/SCID mice after transplantation. Conclusions Our study underscores the importance of a synthetic 3D niche system for the derivation of transplantable hematopoietic cells from human iPSCs in vitro thereby establishing a foundation towards utilization of human iPSC-derived HSCs for transplantation therapies in the clinic.